Revisionnement des séries sur les plateformes de vidéo à la demande - Christine Thoër; Vincent T. Fabre; Sophie Le Berre (Communiquer)
Rewatching a series using video-on-demand (VOD) platforms is becoming increasingly popular. Based on semi-structured interviews with 20 Quebecers aged 18 to 34, this study aims at investigating young adults rewatching practices and their meaning. The results highlight a variety of rewatching practices, most often individual, which are reinforced by the use of connected viewing devices. Marketing strategies of VoD providers as well as platform interfaces offer several incentives to rewatch series and provide users with increased opportunity to control serial text and viewing context.